2009
DOI: 10.1213/ane.0b013e3181acc85d
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Event-Related Potentials, Bispectral Index, and Entropy for the Discrimination of Different Levels of Sedation in Intensive Care Unit Patients

Abstract: Neither ERPs nor BIS or Entropy can replace clinical sedation assessment with standard scoring systems. Discrimination among very deep, deep to moderate, and no sedation after general anesthesia can be provided by ERPs and processed electroencephalograms, with similar P(K)s. The high inter- and intraindividual variability of Entropy and BIS precludes defining a target range of values to predict the sedation level in critically ill patients using these parameters. The variability of ERPs is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Processed electroencephalogram models, such as the bispectral index (BIS monitor-Aspect Medical Systems, Covidien, Mansfield, MA), have been introduced into ICUs that may quantitatively monitor the level of consciousness (62). A recent ICU study suggested a satisfactory correlation between BIS values and validated sedation scales (63), whereas others have refuted it (62)(63)(64)(65). Well-designed clinieal trials are needed to validate a correlation between sedation scales and continuous bedside monitors.…”
Section: Awareness During Induced Paralysismentioning
confidence: 99%
“…Processed electroencephalogram models, such as the bispectral index (BIS monitor-Aspect Medical Systems, Covidien, Mansfield, MA), have been introduced into ICUs that may quantitatively monitor the level of consciousness (62). A recent ICU study suggested a satisfactory correlation between BIS values and validated sedation scales (63), whereas others have refuted it (62)(63)(64)(65). Well-designed clinieal trials are needed to validate a correlation between sedation scales and continuous bedside monitors.…”
Section: Awareness During Induced Paralysismentioning
confidence: 99%
“…Haenggi et al . [25] and other study groups revealed that the BIS reaction to different sedation depths depends on the hypnotics used and shows vast variability. [26272829]…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our study and previous findings, where spectral entropy was correlated to sedation level, entropy measured from frontal EEG had low validity to differentiate clinical sedation state in critically ill patients managed under routine clinical conditions. [2930] The conflicting results in ICU patients may be due to the fact that these patients may have metabolic disorders, encephalopathies, and brain injuries that can affect the EEG. In addition, several centrally acting drugs that confound the EEG signal may be used during ICU sedation.…”
Section: Discussionmentioning
confidence: 99%